House of State Institutions in Irkutsk (House of Soviets) - Lisitsin, Vasily (project baikal, 2023)
The article considers one of the most striking objects of the Soviet period, the House of Soviets, at different stages of its realisation – from its design to final result. On the example of the Irkutsk House of Soviets the peculiarities of the approach to buildings of this type are revealed: architectural competitions, complex environmental approach, stylistic features associated with ideological attitudes, construction problems.